Policies to improve employees' retirement resources - Jonathan Cribb; Carl Emmerson; Paul Johnson; Laurence O'Brien; David Sturrock (Institute for Fiscal Studies (IFS), 2024)
This report discusses how public policy should change to bring about better outcomes in retirement for employees through their accumulation of private pension wealth. In doing so, we draw on new modelling undertaken as part of the Pensions Review (O'Brien, Sturrock and Cribb, 2024) as well as new evidence from public engagement and focus groups undertaken as part of the Review. We focus entirely on policies that affect private sector employees, leaving to one side potential issues with the design of public service pensions. We examine policies that affect the accumulation of defined contribution pension wealth that could be used to fund retirement income, focusing on the parameters of the automatic enrolment system as these have been shown to be powerful in influencing the retirement saving outcomes of private sector employees (Cribb and Emmerson, 2020). New modelling published alongside this report (O'Brien, Sturrock and Cribb, 2024) shows the scale of the challenge facing private sector employees in trying to accumulate private pension wealth. The economic and policy environment has changed significantly over the last two decades, with substantial consequences for retirement saving decisions.
Keywords: 330; Savings; pensions and wealth; Private pensions; Wealth